Analysis of C-Reactive Protein as an Inflammation Indicator in Obese Adolescents - Ubaedillah, Muhammad Ibnu; Ibrahim Aji, Rizal; Ningsih, Trinina Rizkiya Salmiyah (Jurnal Ilmu Kesehatan (JIKSAN), 2025)
Obesity is excessive fat accumulation due to an imbalance between energy intake and energy expenditure, the prevalence of obesity in adolescents is increasing and causing metabolic syndrome. Production of C-Reactive protein (CRP) increases in adolescents with metabolic disorders and at risk of developing cardiovascular disease as adults. This study aims to determine C-Reactive Protein (CRP) in obese adolescents in Susukan Village, Susukan District, Cirebon Regency, and to determine the percentage of obesity that is positive on C-Reactive Protein (CRP) examination. In this study using descriptive methods and for examination using latex agglutination methods. Based on the results of a study of 36 people in Susukan Village, Susukan District, Cirebon Regency, as many as 32 people with a percentage (88.9%) got CRP negative results and 4 people with a percentage (11.1%) got CRP positive results. Based on this study it can be concluded that positive results were obtained on examination of C-reactive Protein (CRP) in obese adolescents in Susukan Village, Susukan District, Cirebon Regency